Fuerstia marisgermanicae gen. nov., sp. nov., an Unusual Member of the Phylum Planctomycetes from the German Wadden Sea - Kohn, Timo; Heuer, Anja; Jogler, Mareike; Vollmers, John; Boedeker, Christian; Bunk, Boyke; Rast, Patrick; Borchert, Daniela; Glöckner, Ines; Freese, Heike M.; Klenk, Hans-Peter; Overmann, Jörg; et al. (Frontiers in Microbiology, 2016)
Members of the phylum Planctomycetes are ubiquitous bacteria that dwell in aquatic and terrestrial habitats. While planctomycetal species are important players in the global carbon- and nitrogen cycle, this phylum is still undersampled and only few genome sequences are available. Here we describe strain NH11T, a novel planctomycete obtained from a crustacean shell (Wadden Sea, Germany). The phylogenetically closest related cultivated species is Gimesia maris, sharing only 87% 16S rRNA sequence identity. Previous isolation attempts have mostly yielded members of the genus Rhodopirellula from water of the German North Sea. On the other hand, only one axenic culture of the genus Pirellula was obtained from a crustacean thus far. However, the 16S rRNA gene sequence of strain NH11T shares only 80% sequence identity with the closest relative of both genera, Rhodopirellula and Pirellula.. Thus, strain NH11T is unique in terms of origin and phylogeny. While the pear to ovoid shaped cells of strain NH11T are typical planctomycetal, light- and electron microscopic observations point towards an unusual variation of cell division through budding: during the division process daughter- and mother cells are connected by an unseen thin tubular-like structure. Furthermore, the periplasmic space of strain NH11T was unusually enlarged and differed from previously known planctomycetes. The complete genome of strain NH11T, with almost 9 Mb in size, is among the largest planctomycetal genomes sequenced thus far, but harbors only 6645 protein-coding genes. The acquisition of genomic components by horizontal gene transfer is indicated by the presence of numerous putative genomic islands. Strikingly, 45 ‘giant-genes’ were found within the genome of NH11T. Subsequent analysis of all available planctomycetal genomes revealed that Planctomycetes as such are especially rich in ‘giant genes’. Furthermore, Multilocus Sequence Analysis (MLSA) tree reconstruction support the phylogenetic distance of strain NH11T from other cultivated Planctomycetes of the same phylogenetic cluster. Thus, based on our findings, we propose to classify strain NH11T as Fuerstia marisgermanicae gen. nov., sp. nov., with the type strain NH11T, within the phylum Planctomycetes.